1999
DOI: 10.1001/jama.282.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Primary Coronary Angioplasty vs Thrombolysis for the Management of Acute Myocardial Infarction in Elderly Patients

Abstract: In elderly patients who present with AMI, primary PTCA is associated with modestly lower short- and long-term mortality rates. In the subgroup of patients who were classified as ideal for reperfusion therapy, the observed benefit of primary PTCA was no longer significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(46 citation statements)
references
References 19 publications
2
42
0
2
Order By: Relevance
“…Several studies have shown that primary PCI (pPCI) in experienced centres is associated with improved outcomes compared with thrombolytic strategies in elderly patients with AMI [35,36]. However, most did not enrol adequate numbers of older patients, and only small trials have specifically addressed the question of fibrinolytic therapy vs PCI in older AMI patients (Table 1) [8,32,[37][38][39][40][41][42].…”
Section: Studies Specifically Comparing Revascularization Procedures mentioning
confidence: 99%
“…Several studies have shown that primary PCI (pPCI) in experienced centres is associated with improved outcomes compared with thrombolytic strategies in elderly patients with AMI [35,36]. However, most did not enrol adequate numbers of older patients, and only small trials have specifically addressed the question of fibrinolytic therapy vs PCI in older AMI patients (Table 1) [8,32,[37][38][39][40][41][42].…”
Section: Studies Specifically Comparing Revascularization Procedures mentioning
confidence: 99%
“…They also have a higher incidence of risk of bleeding than younger patients. Therefore, it was revealed that older patients with AMI are less likely to be treated with reperfusion strategy than younger patients [3,[11][12][13][14]. In 1996, Paul et al [12] reported that the use of thrombolysis was only 9% in 78 patients aged z75 years old whereas the use was 34% in 139 patients aged V65 years.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…7 However, the efficacy of therapy is directly related to the interval between symptom onset and treatment. 8 Patients who receive treatment within the first hour of the onset of symptoms receive the most benefit, but many patients do not receive reperfusion therapy because of excessive delay in seeking evaluation and treatment.…”
mentioning
confidence: 99%